PEMBELAJARAN GUIDED DISCOVERY DALAM UPAYA REMEDIASI MISKONSEPSI MATERI LISTRIK DINAMIS CALON GURU - M. Anas Thohir (Universitas Pendidikan Mandalika, 2015)
This study aims to remediate student misconceptions on dynamic electrical materials. Remediation activities are conducted in two stages. First, the development of guided discovery learning devices and misconception diagnostic test instruments. The development follows the 4-D model stage. The second phase is, the implementation of learning in 35 students of Physics Education in 2011 State University of Surabaya through Design One Group Pretest-Posttest Design. Student misconceptions data were analyzed by CRI analysis and learning implementation data were analyzed by mean of stepping. The data of the research shows that the average value of learning is 3.6 (very good category). Initial misconception profiles are found on every concept before learning and decline after remediation. At the drift speed concept, students experienced misconceptions 66% and 31% after application. In the concept of 'Ohm's law' 26% to 3%, source voltage parallel series strewed 71% to 43%, current consumption model 63% to 46%, series and parallel impact on power 80% to 46%, energy on battery 40% to 37%, electrical circuit typology 69% to 51%, electric power in mixed circuit 51% to 17%, current on a circuit 40% to 11%, potential difference between two points 43% to 9%, use of measuring instrument electricity (ampermeter and voltmeter) in the series 37% to 26%, and Kirchhoff rules 20% to 26%. The results of this data analysis can be concluded that the learning tools developed can reduce student misconception.